Effect of Symptom Over-Reporting on Heart Rate Variability in Veterans With Posttraumatic Stress Disorder. Issue 5 (20th October 2015) - Brady, Robert E.; Constans, Joseph I.; Marx, Brian P.; Spira, James L.; Gevirtz, Richard; Kimbrell, Timothy A.; Kramer, Teresa L.; Pyne, Jeffrey M.
Abstract : Physiological assessment of posttraumatic stress disorder (PTSD) presents an additional avenue for evaluating the severity of PTSD symptoms. We investigated whether the presence of a high number of uncommon symptoms attenuated the relation between self-reported PTSD symptoms and heart rate variability (HRV). Participants were 115 veterans from Operation Iraqi Freedom and Operation Enduring Freedom with or without PTSD. Symptom over-report was assessed using the Miller Forensic Assessment of Symptoms Test (M-FAST). Participants completed the Clinician-Administered PTSD Scale and M-FAST and underwent physiological assessment to determine HRV. These data were then entered into a hierarchical linear regression equation to test the moderating effect of over-reporting on the relation between PTSD symptom severity and HRV. The result of this analysis failed to demonstrate a significant moderating effect of over-reporting on the PTSD and HRV relation. HRV was a significant predictor of PTSD symptom severity, and this relation did not differ across levels of over-reporting. These findings did not support the hypothesis that over-reporting would attenuate the relation between PTSD and HRV. Clinical and research implications and directions for future investigation are discussed.